Baby Einstein: Neighborhood Numbers - Julie Aigner (Malasia Hyperion Book, 2006)
Designed to introduce youngsters to the world of numbersand to assist in the understanding of the significance of numeracy in theireveryday world. With beautifulillustrations of familiar objects, youngsters will learn the world of numbersright outside and inside their door!
Keywords: Board Book -- Board Book